LSOARP: A Link Stability and Obstacle-Aware Routing Protocol for UAV Networks - Almuntadher Mahmood Alwhelat,; Ilyas, Muhammad; Idoko, John Bush Idoko; Lina Jamal Ibrahim,; Mazin S AL-Hakeem,; Sinan Q. Salih, (Journal of Soft Computing and Data Mining, 2025)
As using Unmanned Aerial Vehicles (UAVs) continues to grow across military, environmental, and public safety sectors, we are seeing a fast development of Flying Ad Hoc Networks (FANETs). Despite this progress, creating reliable routing protocols for UAVs remains complex because of their high mobility, constantly changing network topology, frequent link drops, and physical obstacles in the environment. Current protocols often overlook the importance of link stability and obstacle-aware navigation, which can lead to decreased performance in real-world applications.  we present LSOARP: a Link Stability and Obstacle-Aware Routing Protocol customized for UAV networks. This new protocol combines Bézier-curve-based trajectory adjustments for better obstacle avoidance with a multi-criteria link evaluation that considers residual link lifetime, energy efficiency, and route availability. We model UAV movement using a realistic prediction mechanism that captures various states such as high, low, idle, and paused. Routing decisions are then made using a weighted cost function to select the most stable and energy-efficient paths, ensuring strong network performance. Simulation experiments conducted under different conditions—including varying node density, speed, pause times, and traffic loads—show that LSOARP considerably outperforms traditional protocols like RLPR and AODV. It offers higher packet delivery ratios, lower end-to-end delays, reduced energy consumption, and less control overhead. These promising results demonstrate that LSOARP is both scalable and reliable in complex UAV environments, making it a strong candidate for real-time FANET applications.